The Influence of Political Connections on Firm Financial Performance: Does Board of Commissioner Efficacy Matter? - Irvin Valerian Athallah; Agung Juliarto (Diponegoro Journal of Accounting, 2026)
This study was conducted to analyze the influence of political connections on firm financial performance and to examine whether commissioner efficacy moderates this relationship among companies listed on the Indonesia Stock Exchange (IDX). The study employs three theoretical perspectives: Political Economy Theory (Gray et al., 1996), Resource Dependence Theory (Pfeffer & Salancik, 1978), and Agency Theory (Jensen & Meckling, 1976), which collectively explain the dual role of political ties as both strategic resources and potential governance risks. The population in this study comprises non-financial companies consistently listed on the IDX during the observation period, excluding state-owned enterprises (BUMN) and firms lacking complete governance data. A total of 50 companies were obtained as the sample. Data collection was carried out using secondary sources, including annual reports and corporate governance disclosures. The collected data was processed and analyzed using panel regression models with EViews software, incorporating descriptive statistics, correlation matrices, and multivariate regression to test the hypotheses. The results indicate that political connections does not significantly affect firm financial performance and commissioner efficacy does not moderate the influence of political ties on firm outcomes, whether positive or negative. This finding suggests that commissioner effectiveness may not be sufficient to neutralize external political pressures in environments with weak institutional enforcement.